The Symbolic Meaning of Leadership in the Perspective of Symbolic Interaction (Sahbirin Noor's Leadership Style Analysis) - Mardiana MARDIANA (Indonesia Strategic Sustainability, 2023)
Communication problems faced by the government are often related to bureaucratic communication procedures. So, communication activities are needed by leaders in the scope of internal and external communication. This also happened to the province of South Kalimantan, namely H. Sahbirin Noor who served as governor. The purpose of this research is to analyze Me, Mind, and Society leadership and to analyze the governor's self-concept elements in leadership activities, which refers to the symbolic interaction theory. The research approach uses qualitative methods with informants from government and community elements using interviews. The results show that Uncle Birin's self-meaning as a governor generally refers to Government Regulation No. 33 of 2018. Meanwhile, Mind is seen when Uncle Birin chooses a career as a government official for the benefit of the wider community. For the meaning of Society Uncle Birin through an attitude of empathy to be able to understand the wishes of the community. The element of Uncle Birin's self-concept is a visionary leader. Uncle Birin needs a view that fits the reality of society.``Self